Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd006634
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for induction of remission in Crohn's Disease

Abstract: Editorial group: Cochrane Gut Group. Publication status and date: New search for studies and content updated (no change to conclusions), published in Issue 7, 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 17 publications
0
28
0
3
Order By: Relevance
“…Randomised controlled studies in which human adult IBD subjects were treated with herbal therapy were identified. For this systematic review, studies on prebiotics, probiotics fish oils/omega 3‐fatty acids, and moxibustion/acupuncture were excluded as these therapies have been extensively reviewed recently. Studies were included if they were placebo‐controlled or controlled against a conventional treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Randomised controlled studies in which human adult IBD subjects were treated with herbal therapy were identified. For this systematic review, studies on prebiotics, probiotics fish oils/omega 3‐fatty acids, and moxibustion/acupuncture were excluded as these therapies have been extensively reviewed recently. Studies were included if they were placebo‐controlled or controlled against a conventional treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, 2 Cochrane reviews found that probiotics conferred no advantage over placebo in maintaining or inducing remission of CD . Therefore, probiotics are not suggested in the routine maintenance of remission in patients with CD .…”
Section: Microbiota As a Therapeutic Target In Inflammatory Bowel Dismentioning
confidence: 99%
“…No benefit of various probiotic preparations was observed with studies on induction of remission, prevention of recurrence of CD following active disease, or for prevention of post-operative recurrence. [48][49][50] Evidence for extending remission for patients with pouchitis was found, 51,52 but a study by another research group did not find the same product to be effective. 53 A systematic review did not find any benefit to combining probiotics with standard therapy for remission of CD in mild to moderate disease.…”
Section: Use Of Probiotics In Patients With Inflammatory Bowel Diseasementioning
confidence: 99%